Evaluation Of Lipid Peroxidation And The Level Of Some Antioxidants In People Under General Anesthesia - Wasan Ali (College of Education for Pure Sciences, 2010)
ABSTRACT This research includes study of the effects of general anesthesia on lipid peroxide formation and some antioxidant system in serum of patients with appendix surgery. Forty seven patients under general anesthesia with age range of 15-45 years living in Mosul city were selected. The level of serum malondialdehyde (MDA), reduced form of glutathione (GSH), superoxide dismutase (SOD), uric acid, albumin and ceruloplasmin were measured. The results showed a significant increased in MDA level (as an index of lipid peroxidation) in patients under pentothal anesthesia in comparison with preoperative samples. On the other hand, patients under general anesthesia had decreased GSH concentration, SOD activity, uric acid, albumin and ceruloplasmin concentration when compared with preoperative samples.